Mastering the Art of Teaching Secondary Students: Insights, Strategies, Research and AI-Driven Innovations - Levitt, Greg; Grubaugh, Steven (Technium Social Sciences Journal, 2025)
Teaching secondary students requires a multifaceted set of skills that blend pedagogical theory, classroom management techniques, and a deep understanding of adolescent development. Drawing upon insights from veteran educators with several years of experience, this article examines the subtle and often underestimated nuances that contribute to effective teaching in a secondary setting. It highlights core practices that bolster classroom management, student engagement, and instructional differentiation. Moreover, the integration of artificial intelligence (AI) into teaching is explored, revealing how AI-driven tools can offer personalized solutions to classroom challenges. Anecdotes and practical examples illustrate how novice and early career teachers can bridge the gap between emerging instructional methods and the wisdom gleaned from years of hands-on experience. By embracing both tested, instinctive approaches and cutting-edge technologies, educators can foster dynamic and responsive learning environments that empower every student to achieve academic success.